O pacto das águas e suas relações socioambientais com o baixo São Francisco - Matos, Eduardo Lima de (2014)
This thesis deals with THE PACT OF THE WATERS AND ITS SOCIAL AND ENVIRONMENTAL RELATIONS WITH LOWER SÃO FRANCISCO, the methodological approach is the Lower San Francisco located between the Xingó Hydropower Plant and the mouth of the São Francisco River. The study began with the legal bases, correlating constitutional principles, federal and state laws, resolutions and managerial administrative structure of water resources determined under Brazilian law, especially the Watershed Committee, whose powers and duties are analyzed. An index of sustainability of the Lower São Francisco region was made based on the social, environmental, institutional and economic indicators which is demonstrated in a radar chart about the weaknesses and progress in the region, the Methodology used was the one developed by Daniel et al. (2001). Through this index was possible to realize the need for implementing public policies in this region, which have to receive investments to reduce serious and endemic problems. Even though the São Francisco Watershed Committee has collected financial resources, they are not applied in the local. Brazilian legislation created a decentralized and participatory water management system through the watershed Committees structure, which has elastic assignments in the management. This thesis developed mechanisms for ongoing evaluation of the watershed, the sustainability index , from it, founded on the principles of decentralization , participation , legality , proportionality , supremacy of the public interest over private , reasonableness and efficiency, can be done, at the Committee of São Francisco River Watershed, the Water Pact , legal document , approved in the plenary of this Committee which should set the standard use of the funds raised and prioritize investments in critical areas identified in the sustainability index. The Water Pact is the exercise of the Watershed Committee power, and is a symbol of the public interest supremacy.